1982
DOI: 10.1002/jcp.1041120114
|View full text |Cite
|
Sign up to set email alerts
|

A new preadipose cell line derived from newborn mouse calvaria can promote the proliferation of pluripotent hemopoietic stem cells in vitro

Abstract: A clonal preadipose cell line MC3T3-G2/PA6, established from newborn mouse calvaria, responds to glucocorticoids and converts to adipose cells in a fashion similar to bone marrow preadipocytes. We investigated the effect of the cells on in vitro hemopoiesis of mouse bone marrow cells by cocult~vation. When bone marrow cells were inoculated into confluent cultures of MC3T3-G2/PA6 cells (104-106 celM25-cm2 flask), the number of hemopoietic stem cells (CFU-S) significantly increased during 7-day cultivation in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(70 citation statements)
references
References 20 publications
0
69
0
1
Order By: Relevance
“…However, these previous studies were not focused on visceral fat. Recently, two studies have demonstrated the in vitro effects of LF on preadipocytes, where LF suppressed the differentiation of adipocytes in MC3T3-G2/PA6 cell lines 9 derived from the calvaria of mice 10 , as well as the differentiation of 3T3-L1 adipocytes established from a mouse embryo 11 . We reported the effects of bLF metabolites produced in the stomach and small intestine by the digestive enzymes pepsin and trypsin in an in vitro study 12 .…”
Section: Introductionmentioning
confidence: 99%
“…However, these previous studies were not focused on visceral fat. Recently, two studies have demonstrated the in vitro effects of LF on preadipocytes, where LF suppressed the differentiation of adipocytes in MC3T3-G2/PA6 cell lines 9 derived from the calvaria of mice 10 , as well as the differentiation of 3T3-L1 adipocytes established from a mouse embryo 11 . We reported the effects of bLF metabolites produced in the stomach and small intestine by the digestive enzymes pepsin and trypsin in an in vitro study 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Some stromal cell lines, such as MS-5 [32] and PA6 [33], have been reported to have the capacity to support HSCs in vitro. If PA6 is really required for the support of hemopoiesis, all supportive cell lines should express this protein.…”
Section: Discussionmentioning
confidence: 99%
“…Stromal cell lines, such as MS-5, which is established by irradiating adherent cells in long-term BM cultures of C3H mouse [32], and PA6, a clonal preadipose cell line that is established from newborn mouse calvaria, have the capacity to support HSCs in vitro [33]. Therefore, we compared the hemopoiesis-supporting capacity of the FMS/PA6-P cells with these stromal cell lines.…”
Section: Culture Of Hscs On the Fms/pa6-p Cell Line Or Other Stromal mentioning
confidence: 99%
“…Our MC3T3-G2/PA6 preadipocytes, established from newborn mouse calvaria, have a fibroblastic morphology in the growing state and, after entering the resting state, convert to adipocytes (17), showing a hormonal responsiveness similar to that of bone marrow preadipocytes in primary culture (14,15). These cells provide an in vitro microenvironment for CFU-S growth (18). These studies have suggested that some part of the bone marrow fibroblasts differentiate into adipocytes and are important to the hemopoietic microenvironment.…”
mentioning
confidence: 83%